The tenth member of stout newt (Amphibia: Salamandridae: Pachytriton): Description of a new species from Guangdong, southern China - Li, Chen; Yuan, Zhiyong; Li, Haibin; Wu, Yunke (Zootaxa, 2018)
Field surveys of less-explored forests often lead to discoveries of new amphibian species. During a series of field surveys in early 2017 at Mt. Lianhua (the Lotus Mountain) of Lianhuashan-Baipenzhu Provincial Nature Reserve in southern China, we found an undocumented population of stout newt, genus Pachytriton. Based on its distinct morphological characters and large genetic divergence from congeners (uncorrected p-distance > 5% in either mitochondrial nd2 or cytb sequences), we describe this population as the tenth species of the genus: Pachytriton airobranchiatus sp. nov. It can be distinguished from other members of Pachytriton by a combination of the following morphological characters: prominently elevated distal end of the epibranchial bone showing as two conspicuous protruding bulges behind the head; dorsal coloration can be either spotted or unspotted; bright orange dots absent on dorsum; costal grooves absent between axilla and groin; fingers I and toe I slender, do not forms a volar pad; dorsal tips of fingers and toes brown; and tips of fore- and hind limbs could contact when limbs adpressed against body flank. Phylogenetic analysis grouped the new species with P. wuguanfui, P. xanthospilos, and P. changi. Currently, the new species is known from the type locality and an adjacent mountain peak at about 1000 m elevation. It inhabits small montane streams in broadleaf forests near the top of the mountain.